2020
DOI: 10.32604/fdmp.2020.09119
|View full text |Cite
|
Sign up to set email alerts
|

Large Eddy Simulation of Gasoline-Air Mixture Explosion in Long Duct with Branch Structure

Abstract: Gas explosion is a process involving complex hydrodynamics and chemical reactions. In order to investigate the interaction between the flame behavior and the dynamic overpressure resulting from the explosion of a premixed gasoline-air mixture in a confined space, a large eddy simulation (LES) strategy coupled with sub-grid combustion model has been implemented. The considered confined space consists of a long duct and four branches symmetrically distributed on both sides of the long duct. Comparisons between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…RSM and LES have got rid of the isotropic eddy viscosity assumption. Therefore, they can better reproduce main turbulence properties with a higher accuracy, compared with RANS [52][53][54][55]. But for now, the two-equation models are still much more popular.…”
Section: Turbulence Modelsmentioning
confidence: 99%
“…RSM and LES have got rid of the isotropic eddy viscosity assumption. Therefore, they can better reproduce main turbulence properties with a higher accuracy, compared with RANS [52][53][54][55]. But for now, the two-equation models are still much more popular.…”
Section: Turbulence Modelsmentioning
confidence: 99%
“…For a complex pipeline system, lots of research results have been reported on the propagation characteristics of premixed combustible gas explosion in different pipeline structures, such as curved pipelines, parallel pipe networks, , and so on. For a pipeline with branches, studies include the influence of the number and relative setting position of branches on explosion overpressure as well as the propagation characteristics of explosion overpressure in branches, , results of which show that sudden area expansion and turbulence at bifurcation can enhance the explosion pressure. What is more, the influence study of bifurcated pipes with different angles on explosion shows that overpressure produced by shock waves is greater in a pipeline with an obtuse angle branch. , In addition, vortex groups and greater turbulence intensity are more likely to be produced in a flow system with a horizontal 90° branch structure because the diversion effect of the three-way pipe increases the explosion pressure release channel . Further, larger turbulence will increase explosion overpressure, and the maximum explosion pressure increases linearly with the increase of turbulence intensity .…”
Section: Introductionmentioning
confidence: 99%
“…For a complex pipeline system, lots of research results have been reported on the propagation characteristics of premixed combustible gas explosion in different pipeline structures, such as curved pipelines, 2 4 parallel pipe networks, 5 , 6 and so on. For a pipeline with branches, studies include the influence of the number and relative setting position of branches on explosion overpressure as well as the propagation characteristics of explosion overpressure in branches, 7 , 8 results of which show that sudden area expansion and turbulence at bifurcation can enhance the explosion pressure. 9 11 What is more, the influence study of bifurcated pipes with different angles on explosion shows that overpressure produced by shock waves is greater in a pipeline with an obtuse angle branch.…”
Section: Introductionmentioning
confidence: 99%
“…Fire or explosion of aircraft fuel systems is one of the main causes of aircraft crashes [1,2]. During the flight once the fuel vapor is mixed with oxygen-enriched air (OEA) in the aircraft fuel tank encounters ignition sources such as electric sparks or external fire attack, it will cause combustion and even lead to explosion [3]. The aircraft fuel tank inerting system uses air separation technology to produce nitrogenenriched air (NEA), and uses the generated NEA to wash or flush the upper space of the fuel tank, to ensure that the oxygen concentration in the upper space of the aircraft fuel tank is within the safety limit.…”
Section: Introductionmentioning
confidence: 99%